DECLARING THAT EXTRA-STATUTORY GUIDANCE VIOLATES CONVENTION RIGHTS. (5th July 2016) - Feldman, David
Abstract : SECTION 3(2) of the Immigration Act 1971 requires the Home Secretary to lay down Immigration Rules regulating "entry into and stay in the United Kingdom" by "persons required by this Act to have leave to enter". The rules are glossed by voluminous, extra-statutory, internal guidance and Immigration Directorate Instructions (hereafter referred to as "guidance") drawn up in the Home Office.